Rheological Behaviour Of Coconut Milk: Effects Of Concentration And Temperature - Muda@Omar, Noraziah (2002)
The rheological behaviour of coconut milk was studied using a Haake rotational viscometer having a concentric cylinder geometry sensing system. The rheological model of coconut milk, incorporating the effects of concentration and temperature was developed. Experiments were conducted at 4 levels of temperatures in the range of 5°C to 65°C and 6 levels of concentrations ranging from 10 % to 50 % total solid (TS) . The hysteresis effect was examined by varying the shear rate in an ascending order from IS-I to 1000 S-1 followed by a descending order (1000 s-1 to Is- 1 ) . The coconut milk, within the ranges of concentration and temperature studied, exhibited different rheological behaviours. Two rheological models, namely the Newtonian and Power Law model were applied to fit the experimental data. The coconut milk with concentrations of lower than 2 5% TS exhibits Newtonian behaviour. For TS of between 2 5% to 50 %, coconut milk behaves more like a Power L aw fluid. Coconut milk that exhibits Newtonian behaviour was of low concentration while coconut milk that follows the Power Law model was of high concentration. The apparent viscosity for low concentration coconut milk showed an exponential type dependence on the concentration while the effect of temperature on the apparent viscosity obeyed the Arrhenius type relations hip. The high concentration coconut milk was of a s hear thinning fluid with a flow behaviour index , n = 0.567. The flow behaviour index was not significantly affected by the concentration and the temperature in the study. The effect of temperature on the consistency coefficient in Power Law model obeyed the Arrhenius type equation. The effect of concentration on the consistency coefficient obeyed an exponential type equation. The general mathematical models were developed to represent the combined effects of concentration and temperature for low concentration as well as for high concentration coconut milk . Each model developed showed accurate prediction of shear rate. The magnitude of the activation energy, Ea for low concentration coconut milk was 3 720.03 cal/mol which was lower than that of high concentration coconut milk (4236.63 cal/mol). An F-tes t was carried out on the magnitude of s hear s tress for ascending and descending order s hear rates for high concentration coconut milk irrespective of concentration, temperature and shear s tress . The test showed that there was no significant difference in the magnitude of shear stress . This indicates that there is no significant effect of time on the rheological behaviour of coconut milk .